2021
DOI: 10.1016/j.colsurfb.2020.111405
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica nanoparticles containing silver as novel antimycobacterial agents against Mycobacterium tuberculosis

Abstract: Tuberculosis remains today a major public health issue with a total of 9 million new cases and 2 million deaths annually. The lack of an effective vaccine and the increasing emergence of new strains of Mycobacterium tuberculosis (Mtb) highly resistant to antibiotics, anticipate a complicated scenario in the near future. The use of nanoparticles features as an alternative to antibiotics in tackling this problem due to their potential effectiveness in resistant bacterial strains. In this context, silver nanopart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…Several studies underline that MSN have a great potential as drug delivery system in tuberculosis therapy. [24][25][26][27] Regarding tuberculosis therapy with AMPs, Tenland et al could show that the encapsulation of the AMP NZX within MSN could enhance the antimicrobial activity against Mycobacterium bovis (BCG) in vitro and Mycobacterium tuberculosis H37Rv in vivo. [27] Dendritic mesoporous silica nanoparticles (DMSN) a subclass of MSN have been demonstrated to be excellent candidates for drug delivery due to good synthetic control over important particle characteristics, like particle and pore diameter, specific surface area, and pore volume.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies underline that MSN have a great potential as drug delivery system in tuberculosis therapy. [24][25][26][27] Regarding tuberculosis therapy with AMPs, Tenland et al could show that the encapsulation of the AMP NZX within MSN could enhance the antimicrobial activity against Mycobacterium bovis (BCG) in vitro and Mycobacterium tuberculosis H37Rv in vivo. [27] Dendritic mesoporous silica nanoparticles (DMSN) a subclass of MSN have been demonstrated to be excellent candidates for drug delivery due to good synthetic control over important particle characteristics, like particle and pore diameter, specific surface area, and pore volume.…”
Section: Introductionmentioning
confidence: 99%
“…On a very recent contribution Montalvo-Quirós et al studied the different performance of both approaches reviewed so far: a core-shell structure in which a big AgNP is coated by a silica layer and model that grows AgNPs within the mesopores. 88 Both structures were prepared successfully and tested against M. tuberculosis . It was found that the approach onto AgNPs were grown at the mesopores had a higher antibiotic effect that could be assumed to be consequence of an increased dissolution rate of AgNPs together with a more intimate contact between particles and mycobacteria.…”
Section: Antibacterial Effects Of Metal-doped Msnsmentioning
confidence: 99%
“…In recent decades, uncontrolled drug use has led to major public health, economic, and environmental problems. As a result, bacteria, as well as other microorganisms, have acquired or developed unfavorable resistance mechanisms toward conventional drugs [ 1 ]. The World Health Organization (WHO) has launched a priority list of bacteria that should be studied more rigorously, and all the bacteria on this list are resistant to various drugs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%